Practical guidance for combination lipid-modifying therapy in high- and very-high-risk patients: A statement from a European Atherosclerosis Society Task Force - Averna, Maurizio; Banach, Maciej; Bruckert, Eric; Drexel, Heinz; Farnier, Michel; Gaita, Dan; Magni, Paolo; März, Winfried; Masana, Luis; Mello E Silva, Alberto; Reiner, Zeljko; Ros, Emilio; et al. (Atherosclerosis, 2021)
BACKGROUND AND AIMS: This European Atherosclerosis Society (EAS) Task Force provides practical guidance for combination therapy for elevated low-density lipoprotein cholesterol (LDL-C) and/or triglycerides (TG) in high-risk and very-high-risk patients. METHODS: Evidence-based review. RESULTS: Statin-ezetimibe combination treatment is the first choice for managing elevated LDL-C and should be given upfront in very-high-risk patients with high LDL-C unlikely to reach goal with a statin, and in primary prevention familial hypercholesterolaemia patients. A proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor may be added if LDL-C levels remain high. In high and very-high-risk patients with mild to moderately elevated TG levels (>2.3 and < 5.6 mmol/L [>200 and < 500 mg/dL) on a statin, treatment with either a fibrate or high-dose omega-3 fatty acids (icosapent ethyl) may be considered, weighing the benefit versus risks. Combination with fenofibrate may be considered for both macro- and microvascular benefits in patients with type 2 diabetes mellitus. CONCLUSIONS: This guidance aims to improve real-world use of guideline-recommended combination lipid modifying treatment.
Keywords: anticholesteremika; Combination treatment; statiny; Triglycerides; Cholesterol, LDL; Humans; proproteinkonvertasa subtilisin/kexin typu 9; 2019 ESC/EAS Dyslipidaemia Guidelines; LDL cholesterol; Hydroxymethylglutaryl-CoA Reductase Inhibitors; High-risk; ateroskleróza; lidé; Anticholesteremic Agents; LDL-cholesterol; Diabetes Mellitus, Type 2; Lipid goals; Atherosclerosis; Proprotein Convertase 9; diabetes mellitus 2. typu